PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 178 PEKANBARU - Ade Nur Azni; Zariul Antosa; Munjiatun Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this research was the lowlearning achievement IPS, caused by still using the old paradigm and the teachers imparted knowledge to the students passively. The teachers did not link students with learning experiences that ware being learned and the teacher failed to give an opportunity to the students to express their ideas with own language and that learning becomes unconducive. The teachers less varied in using media, methods, and approaches existing learning. Cooperative LearningtypeNHT can improve learning achievement IPS fourth grade students of SDN 178 Pekanbaru. Subjects in this research is the fourth grade students of SD Negeri 178 Pekanbaru 2014/2015 period with 32 participated. Design of this research was Action Research (PTK) done in two cycles, each cycle is done twice with a repeat meeting with one end of a cycle. This research aims to improve learning achievement IPS fourth grade students of SDN 178 Pekanbaru. The results showed that the application of cooperative learning type NHT could improve learning achievement IPS fourth grade students of SDN 178 Pekanbaru. At the beginning of the data base score of 60.78, in the first cycle increased to 71.88 from the initial data. In the second cycle increased the result into 83.28. Based on the result it can be concluded that the application of cooperative learning type NHT could improve learning achievement IPSfourth grade students of SDN 178 Pekanbaru.Keywords: Cooperative Learning Type NHT, LearningAchievement IPS